Improvement of Torque Capability of Direct Torque Control of Induction Machines - Auzani Jidin; New Lai Sim; Tole Sutikno (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
A control strategy for overmodulation operation of direct torque control hysteresis based in induction machine is proposed. The strategy is to extend the constant torque region as well as to improve the torque capability. The proposed overmodulation strategy is different to SVM based system where the reference stator voltage is available. In order for DTC hysteresis based system to be able to achieve that, several modifications have been applied so that the proposed overmodulation can be achieved by gradually transforming the PWM voltage waveform to six-step mode. Simulated results were provided to demonstrate the effectiveness of the strategy.